Tracking the footprints of the quingnam language - Solís Fonseca, Gustavo (2015)
Taking into account the seventeenth century handwritten document, recently (2008-2010) discovered in Santa Maria Magdalena de Cao (Trujillo) and referring to the extinct quingnam language, this article examines the list of number names contained in it to recognize the numbering system, as well as the cultural implications and what can be inferred about aspects of the grammatical organization of the language. It also highlights the signs of contact between the quechua and quingnam languages.